Factors Influencing Firm Performance Among Traditional Chinese Medicine In China: Mediating And Moderating Effect Of Internationalization And Government Support - Yiliang, Yuan (2022)
With the deepening of the market economy, leading industries play a more critical role in developing a national economy. Traditional Chinese medicine as a top industry, traditional Chinese medicine has stagnated in recent years, facing slow development and bankruptcy problems. Therefore, how to promote the performance development of small and medium-sized enterprises of traditional Chinese medicine and give full play to the role of small and medium-sized enterprises of traditional Chinese medicine in national development is a significant problem to be solved urgently. Talent (TA), technical capability (TC), and marketing capability (MC) are the biggest problems faced by small and medium-sized enterprises of traditional Chinese medicine in the process of development. Based on the resource-based view (RBV) theory, TA, TC, and MC generally consider resources that affect enterprise performance. Therefore, TA, TC, and MC were independent variables in this study. With economic globalization, internationalization is the company's intangible asset, bringing more resources, making the company more extensive internal resource allocation, and having more substantial international competitiveness. Therefore, this study regards internationalization as an intermediary variable. However, previous studies have not found the relationship between these independent variables and internationalization. This study assumes that government support can strengthen the relationship between these variables and internationalization, so government support is used as a moderating variable. Relevant studies show that establishing cooperative relations between the government and enterprises and active support for enterprises will promote the internationalization process of small and medium-sized enterprises